(untitled) (The Pakistan Development Review, 2001)
It has been long debated in economic literature whether financial markets play a significant role in economic growth and development. [For review see Gertler (1988) and Levine (1997)]. Findings of some recent empirical literature show that well-functioning financial system plays an instrumental role in economic growth, and the causality runs from finance to growth [for cross country evidences see King and Levine (1993, 1993a); Levine and Zervos (1998); Levine, Loayza and Beck (1999); Beck, Levine, and Loayza (1999)]. This, in turn, has led to a search for the key factors that determine the better functioning financial markets. Within the banking sector, efficiency is the core concern of both academics and bank officials. A number of studies have sought to measure the efficiency of financial institutions, to identify the factors that contribute to efficiency of financial system, and to recommend the ways to attain the peer group efficiency levels [Berg (1993); Leaven (1999); Berger and Mester (1997); Miller and Noulas (1996)].